Exploring barriers to lung cancer patient access, diagnosis, referral and treatment in Kwazulu-Natal, South Africa: the health providers’ perspectives - Lubuzo, Buhle (Transl Lung Cancer Res, 2019)
BACKGROUND: The burden of cancer is increasingly emerging as a key public health problem in South Africa. This burden is aggravated by low suspicion index by patients and healthcare providers alike, limited financial and human resource investment, weak healthcare systems, and limited quality care. Patients typically present to health facilities very late, resulting in poor treatment outcomes, hence there is a pervasive hopelessness associated with a diagnosis of lung cancer in South African public health systems. Research on the barriers to lung cancer patient care, especially from the perspectives of the healthcare professionals, is limited. Therefore, the aim of this study was to explore the health professionals’ understanding and experiences on the barriers to lung cancer care in the three health facilities providing oncology services in KwaZulu-Natal, South Africa. METHODS: This was a grounded theory study comprising of 18 health providers (seven specialist oncologists, four radiotherapists, one pulmonologist, two social workers, one psychologist and three nurses) from three health facilities providing oncology services in KwaZulu-Natal. Theoretical saturation was achieved at 19 in-depth interviews with consenting participants. In-depth interview transcripts were thematically analysed. RESULTS: The in-depth interviews generated rich data on the diverse issues regarding barriers to lung cancer care. The healthcare professionals perceived limited access to oncology services and poor diagnosis, as some of the leading barriers to effective lung cancer care. Lack of psycho-social and supportive care, resources and basic infrastructure mean that, for most patients, there is limited access to lung cancer screening, early diagnosis, treatment and/or palliative care. CONCLUSIONS: The public sector faces infrastructural and key personnel shortages. Therefore, infrastructural and human resource challenges should be prioritised by policy-makers and administrators. Additionally, the vital contributions of psycho-social professionals should be incorporated in policies and programs supporting cancer care, in order to improve the cancer patient care. The results of this study may help decision makers to further improve cancer care in South Africa.